Bauru: terra de cerrado ou floresta? - Cavassan, Osmar [UNESP] (My University, 2013)
Bauru: region of cerrado ou forest? The city of Bauru is located in São Paulo State, where the maps showing native vegetation distribution does not clearly defi ne its nature. In order to clarify which types of native vegetation was found in this region, a bibliographic survey was performed, ranging from ancient documents prepared by naturalists describing this region and recent research results of floristic and phytosociological character. It is concluded that in Bauru, semideciduous seasonal forests overlays the northwestern and that cerrado comes over the southeast region. In riparian areas where the cerrado prevailed, there are still traces of swamp forests and swamp grasslands. In the border areas between forests and cerrado, the occurrence of vegetation transition is common, with two distinct types of it and other typical of these ecotone zones.

Bauru: terra de cerrado ou florestas? O município de Bauru localiza-se no interior do estado de São Paulo, onde os mapas que mostram a distribuição da vegetação nativa, não defi nem claramente qual a sua natureza. Com o objetivo de esclarecer quais tipos de vegetação nativa ocorriam nesta região, fez-se um levantamento bibliográfico, desde documentos antigos elaborados por naturalistas que descreveram esta região, até resultados de pesquisas recentes de caráter florístico e fitossociológico. Conclui-se que em Bauru, as matas estacionais semideciduais recobriam a região noroeste do Município e o cerrado a região sudeste. Nas áreas ribeirinhas onde predominava o cerrado, ainda existem vestígios de matas e campos paludosos. Nas áreas limítrofes entre matas e cerrados, é comum a ocorrência de vegetação de transição, com espécies dos dois tipos de vegetação distintos e outras típicas destes ecótones.
Bauru: region of cerrado or forest?
Keywords: Native vegetation; Vegetation fragments; Vegetation mosaic; Savanna woodland; Semideciduous seasonal forest; Swamp forest; Vegetação nativa; Fragmentos vegetacionais; Mosaico vegetacional; Savana florestada; Floresta estacional semidecidual; Floresta paludosa